2012
DOI: 10.1007/s10875-011-9640-5
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Bound Toll-Like Receptors are Overexpressed in Peripheral Blood and Synovial Fluid Mononuclear Cells of Enthesitis-Related Arthritis Category of Juvenile Idiopathic Arthritis (JIA–ERA) Patients and Lead to Secretion of Inflammatory Mediators

Abstract: We examined expression and function of TLRs in enthesitis-related arthritis (ERA) patients. RNA levels of TLR1, TLR3, and TLRs 5–8 were measured in 24 ERA peripheral blood mononuclear cells (PBMC), 18 synovial fluid mononuclear cells (SFMC), and IRAK1, IRAK4, TRIF, TRAF3, and TRAF6 in 18 PBMC and 10 SFMC. IL-6 and IL-8 were measured in supernatants from ERA PBMC (n=7), SFMC (n=3), and healthy PBMC (n=5) cultured with ligands for TLR1/2 (Pam 3-cys), TLR3 (polyI:C), TLR5 (flagellin), and TLR2/6 (zymosan). TLRs 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
1
3
0
1
Order By: Relevance
“…Indeed, we have previously demonstrated that the TLR3-IFN-β pathway is desensitized in MS patient PBMCs, suggesting that MS patients may be pre-sensitized to viral infection showing some form of TLR3 tolerance. However, the non-responsiveness of healthy donor PBMCs to poly(I⋅C) is in line ( Wesch et al, 2006 ) and in contrast ( Myles et al, 2012 ) to findings elsewhere in studies which investigated freshly isolated PBMCs; differences in dose and timecourse for treatment regimen used with poly(I:C) in the present study may underlie the differences observed.…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, we have previously demonstrated that the TLR3-IFN-β pathway is desensitized in MS patient PBMCs, suggesting that MS patients may be pre-sensitized to viral infection showing some form of TLR3 tolerance. However, the non-responsiveness of healthy donor PBMCs to poly(I⋅C) is in line ( Wesch et al, 2006 ) and in contrast ( Myles et al, 2012 ) to findings elsewhere in studies which investigated freshly isolated PBMCs; differences in dose and timecourse for treatment regimen used with poly(I:C) in the present study may underlie the differences observed.…”
Section: Discussionsupporting
confidence: 79%
“…TRAF3 expression is up-regulated in synovial fluid mononuclear cells and PBMCs of patients with juvenile idiopathic arthritis, and genome-wide association studies (GWASs) identified TRAF3 as a susceptibility gene for human multiple sclerosis [142,143]. A PTP22 variant (PTPN22_R620W) that is strongly associated with human SLE and RA fails to promote TRAF3 ubiquitination [126].…”
Section: Traf3mentioning
confidence: 99%
“…It targets NFκB regulation by inhibiting IRAK1 and TRAF-6, leading to a reduction of the downstream production of various inflammatory mediators (TNFα and IL-1β) [102,[106][107][108][109][110]. The ERA subtype of JIA features an increased mRNA expression of IRAK4, IRAK1 and TRAF-6 in peripheral blood and synovial fluid mononuclear cells [111]. In addition, several studies suggest that miR-146a and IRAK1 polymorphism equates to a possible susceptibility to inflammatory arthritic diseases, especially ERA [108,[110][111][112].…”
Section: Mirnasmentioning
confidence: 99%
“…The ERA subtype of JIA features an increased mRNA expression of IRAK4, IRAK1 and TRAF-6 in peripheral blood and synovial fluid mononuclear cells [111]. In addition, several studies suggest that miR-146a and IRAK1 polymorphism equates to a possible susceptibility to inflammatory arthritic diseases, especially ERA [108,[110][111][112].…”
Section: Mirnasmentioning
confidence: 99%